The influence of csr on earning management by considering the antecedent variables of csr disclosure, csr performance, and ceo ability - Nabila, Nabila; Saiful, Saiful (Enrichment : Journal of Management, 2023)
This research aims to investigate the influence of Corporate Social Responsibility (CSR) on earnings management practices by considering antecedent variables, such as CSR Disclosure, CSR Performance, and the Chief Executive Officer (CEO) ability. The research method used a quantitative approach with panel data from 2017 to 2022, involving non-financial companies listed on the Indonesian Stock Exchange. The results of data analysis indicate that CSR Disclosure (CSRD), CSR Performance (KCSR), and CEO Ability (CSRA) influence earnings management practices. The classical assumption test validates normality, without multicollinearity, autocorrelation, and heteroscedasticity in the model. The coefficient of determination (R^2) is 4,3%, indicating that the three independent variables explain a small portion of the variation in earnings management. The F statistical test confirms the significance of the influence of independent variables on earnings management. The individual parameter test shows that CEO Ability (CSRA) has no significant influence, while CSR Performance (KCSR) and CSR Disclosure (CSRD) have a negative and significant influence on earnings management practices. In conclusion, earnings management practices are influenced by CSR Performance and CSR Disclosure, but not by CEO Ability.